Effects of live-shearing on population parameters and movement in sedentary and migratory populations of guanacos Lama guanicoe - Carmanchahi, Pablo Daniel (2014)
Live-shearing of wild guanacos Lama guanicoe may affect their reproductive success and population resilience, and therefore it is important to assess the biological sustainability of obtaining their wool. We evaluated effects of capture and shearing on survival and reproduction, population parameters, daily movements, ranging behaviour and spatial distribution in sedentary and migratory populations. We assessed population variables by radio-telemetry and line-transect surveys before and after capture. We estimated high post-shearing survival rates in both populations and similar yearling production in shorn and non-shorn females in the migratory population. We did not find significant variations in density and population structure before and after shearing in the sedentary population, whereas in the migratory population density decreased and the population structure changed significantly after assembly of the capture structure, returning to pre-assembly levels 1 month later. The mean daily distance moved by radio-collared guanacos during the first 2 days after shearing was three times longer than during the following 30 days. There was a 25% decrease in the mean home-range size of shorn guanacos between the first and second month after shearing but this decline appeared to be associated with a seasonal change in movement, because a similar reduction occurred during the same period the following year, when the guanacos were not shorn. Live-shearing modified the spatial distribution pattern in the sedentary population but did not have a significant effect on the migratory population.Management of guanacos may contribute towards developing a biologically sustainable economic activity that promotes conservation of wildlife and habitats.